Анализ взаимодействия импульсных электромагнитных полей с вредителями плодовых культур - Адамова, С. В. (НТУ "ХПИ", 2009)
Получено интегральное уравнение для расчетов электромагнитного поля внутри биологических объектов.

The integral equation for computation of biological objects electromagnetic field is proposed.
Analysis of pulse electromagnetic fields interaction with wreckers of fruit crops
Keywords: насекомое-вредитель; ЭМП; электромагнитное излучение; pulse electromagnetic field; integral equation; biological objects; influence